Activation of WIP1 Phosphatase by HTLV-1 Tax Mitigates the Cellular Response to DNA Damage - Dayaram, Tajhal (Public Library of Science, 2013)
Genomic instability stemming from dysregulation of cell cycle checkpoints and DNA damage response (DDR) is a common feature of many cancers. The cancer adult T cell leukemia (ATL) can occur in individuals infected with human T cell leukemia virus type 1 (HTLV-1), and ATL cells contain extensive chromosomal abnormalities, suggesting that they have defects in the recognition or repair of DNA damage. Since Tax is the transforming protein encoded by HTLV-1, we asked whether Tax can affect cell cycle checkpoints and the DDR. Using a combination of flow cytometry and DNA repair assays we showed that Tax-expressing cells exit G(1) phase and initiate DNA replication prematurely following damage. Reduced phosphorylation of H2AX (γH2AX) and RPA2, phosphoproteins that are essential to properly initiate the DDR, was also observed in Tax-expressing cells. To determine the cause of decreased DDR protein phosphorylation in Tax-expressing cells, we examined the cellular phosphatase, WIP1, which is known to dephosphorylate γH2AX. We found that Tax can interact with Wip1 in vivo and in vitro, and that Tax-expressing cells display elevated levels of Wip1 mRNA. In vitro phosphatase assays showed that Tax can enhance Wip1 activity on a γH2AX peptide target by 2-fold. Thus, loss of γH2AX in vivo could be due, in part, to increased expression and activity of WIP1 in the presence of Tax. siRNA knockdown of WIP1 in Tax-expressing cells rescued γH2AX in response to damage, confirming the role of WIP1 in the DDR. These studies demonstrate that Tax can disengage the G(1)/S checkpoint by enhancing WIP1 activity, resulting in reduced DDR. Premature G(1) exit of Tax-expressing cells in the presence of DNA lesions creates an environment that tolerates incorporation of random mutations into the host genome.